2017
DOI: 10.3389/fncel.2017.00218
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Matrix Metalloproteinase-9 in Primary Cultured Rat Astrocytes Induced by 2-Chloroethanol Via MAPK Signal Pathways

Abstract: 2-Chloroethanol (2-CE) is one of the reactive metabolites of 1,2-DCE in vivo, which might contribute to brain edema formation induced by 1,2-dichloroethane (1,2-DCE) poisoning. Thus, the purpose of this study was to explore the roles of mitogen-activated protein kinase (MAPK) signal pathways in upregulation of matrix metalloproteinase-9 (MMP-9) in 2-CE exposed rat astrocytes. Expression of p38 MAPK (p38), extracellular signal regulated protein kinase (ERK), c-Jun N-terminal kinase (JNK) and MMP-9 at both prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
(55 reference statements)
2
22
0
1
Order By: Relevance
“…A number of studies have demonstrated that MAPKs regulate the MMP‐2/‐9 activation, leading to regulatory cell migration and invasion 48,49 . Our results show that the effects of POMx are mediated by activating ERK1/2 signaling, but not by the JNK and p38 signaling (Figure 7).…”
Section: Discussionmentioning
confidence: 53%
“…A number of studies have demonstrated that MAPKs regulate the MMP‐2/‐9 activation, leading to regulatory cell migration and invasion 48,49 . Our results show that the effects of POMx are mediated by activating ERK1/2 signaling, but not by the JNK and p38 signaling (Figure 7).…”
Section: Discussionmentioning
confidence: 53%
“…It is well known that up-regulated expression of MMP-9 could contribute to disruption of the blood brain barrier integrity. Moreover, findings from our studies have disclosed that activated Mitogen Activated Protein Kinase (MAPK) signal pathways were implicated in the modulation of proinflammatory factors, such as MMPs, iterleukins and tumor necrosis factor, AQPs, tight junction proteins during course of brain edema induced 1,2-DCE poisoning (Sun et al, 2016a ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 95%
“…The process of tumor invasion relies on the precise coordination of extracellular matrix adhesion and hydrolysis in association with two members of the matrix metalloproteinase (MMP) family; namely MMP-2 and MMP-9. The expression of MMPs is primarily controlled by MAPK and other signaling pathways, including the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway (46). This has been validated by a number of studies in which the inhibitory functions of anticancer drugs on tumor invasion and metastasis were demonstrated to occur by downregulating the MAPK signaling pathway, which resulted in reduced expressions of MMPs (47,48).…”
Section: Action Mechanisms Of the Mapk Signaling Pathway In Oral Cancermentioning
confidence: 88%